Silencing the Sounded Self : John Cage and the American Experimental Tradition - Shultis, Christopher (Book collections on Project MUSE., 2013)
Christopher Shultis has observed an intriguing contrast between John Cage's affinity for Thoreau and fellow composer Charles Ives's connection with Emerson. Although both Thoreau and Emerson have been called transcendentalists, they held different views about the relationship between nature and humanity and about the artist's role in creativity. Shultis explores the artist's "sounded" or "silenced" selves-the self that takes control of the creative experience versus the one that seeks to coexist with it-and shows how recognizing this distinction allows a better understanding of Cage. He then e.